The Reality of Teachers’ Use of Modern Technologies in Teaching Arabic as a Second Language in Terms of Objectives and Selection Foundations at the Institute of Arabic Language in Umm Al-qura University Mamoun Eltigani Hassan Eldali (Journal of the College of Education for Women, 2022)
This study aims to know the degree of importance and the availability of the enhancing specifications of the educational process, and the way its objectives are achieved. Such a step involves using educational techniques, laying the selection foundations, knowing the methods of their employment and tracking the obstacles that limit this employment in teaching Arabic to non-native speakers. To achieve these objectives, the study followed a descriptive approach, and collected the necessary data through an integrated questionnaire prepared for the purpose of describing the phenomenon or topic. This approach was adopted, as it is characterized by being comprehensive, focuses on collecting data related and necessary to the topic under study. It further suits research papers that deal with educational problems. The study has concluded that modern educational technologies are highly recommended to be used in teaching languages. Such technologies further meet the learners’ needs in terms of achieving special and behavioral goals, supporting the educational content, and activating the teaching methods to achieve the general goals of the educational process if attention was paid to the way they are used and to their governing rules. The study has also concluded that the most important obstacles in teaching using technology are lack of training, ignorance and lack of knowledge of the methods and of employing them in the educational situation. The study has recommended the necessity of having a good preparation for the educational process based on technology, and working to provide, update and follow-up on its maintenance. More so, the interest in teaching Arabic to non-native speakers through employing modern technologies in proportion to its elements and skills should be enhanced.